The Impact of Flight Operation Load During Pre-Covid, During Covid, and Post-Covid in Asia Aeronautical Training Academy (AATA) - Engku Muhammad Azmi, Engku Sofiah; Abdul Ghafir, Mohammad Fahmi (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The Covid-19 pandemic that has been spreading in the world has been affecting all types of the industry starting from its emergence and the aviation industry is one of the hardest-hit industries by the pandemic. One of the type of organizations in the aviation industry that is also affected by the pandemic and all of the restriction that has been imposed in the world to contain the spreading of the pandemic is the flight training organization. This study was conducted to study how Covid-19 has affected the AFTO in Malaysia, specifically in AATA. This study will analyze the flight usage, the fuel consumption, the fuel cost and the impact of the flight training from the data of the flight training which was obtained from FlightLogger.com and the fuel price which was obtained from index mundi.com. The data was collected starting from November 2019 to May 2022 where it was divided into three different periods which are pre-Covid, during Covid, and post-Covid. In conclusion, the highest number of flight usage was in April 2022, which is the post-Covid period, however, the highest amount of fuel consumption was in April 2021, which has the second-highest number of flight usage. The fuel cost analysis has discovered that the highest fuel cost was in April 2022 which has the second-highest fuel price. The aircraft emission was lower in the Covid period than in the post-Covid period, which means that air quality in the Covid period is higher.